Measurement of Leukocyte telomere length with various modifications to Cawthon's method: a review - Al-Battawi, Samer; Ho, Yu Bin; Latif, Mohd Talib; How, Vivien; Thilakavathy, Karuppiah (Faculty of Medicine and Heallth Sciences, Universiti Putra Malaysia, 2022)
Telomeres are non-coding folded-loop DNA structures that are capped the chromosomes’ ends in order to protect them against any damage. Leukocyte telomere length (LTL) shortening represents a biological ageing marker that is linked to the morbidity as well mortality. Cawthon’s method of measuring LTL using quantitative real-time PCR has emerged and become phenomenal due to its important features such as affordability, rapidity, and convenience. However, various modifications were introduced to Cawthon’s method, such as the number of replicates, PCR profile, concentration of primers, and quality control steps. This review addresses all these modifications and their effects on the measurement of LTL and provides an overview for the researchers who want to assess the LTL in their studies. In addition, some effects of LTL on human health issues are elaborated in this review.